2011
DOI: 10.1177/1066896910382005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Immunohistochemistry for p16INK4 and High-Risk HPV DNA by In Situ Hybridization in Esophageal Squamous Cell Carcinoma

Abstract: The role of high-risk human papillomavirus (HPV) in the pathogenesis of esophageal squamous cell carcinoma (ESCC) remains unclear. p16(INK4) is used as a surrogate marker to detect HPV-related tumors but has had discrepant results in ESCC. In this study, 32 cases of ESCC were examined to determine the relationship between p16(INK4) expression and high-risk HPV. All the tumors were stained by immunohistochemistry for p16(INK4). Tumors having p16(INK4) nuclear and/or nuclear and cytoplasmic expression were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In general, studies conducted in high‐risk regions for ESCC incidence, have reported higher rates of HPV in ESCC specimens than studies that are carried out in low‐risk regions. Many of the most recent studies continue to support this trend . However, there have been some exceptions to this pattern.…”
Section: Resultsmentioning
confidence: 95%
“…In general, studies conducted in high‐risk regions for ESCC incidence, have reported higher rates of HPV in ESCC specimens than studies that are carried out in low‐risk regions. Many of the most recent studies continue to support this trend . However, there have been some exceptions to this pattern.…”
Section: Resultsmentioning
confidence: 95%
“…37 And while 14 studies have reported on expression of p16 INK4a protein in ESCC tissues, they used varying cut-offs to define p16 INK4a positivity and reported contradicting results. 15,34,[38][39][40][41][42][43][44][45][46][47][48][49] As a result of inconsistent HPV DNA data and very limited direct functional evidence provided in the last 30 years of research, the worldwide expert panel of the 100 th IARC Monograph concluded that the evidence for a causal association between HPV and ESCC remains inconclusive. 4 In addition to HPV functional markers that can be assessed in tumor tissues, antibodies to HPV early proteins, especially E6 and E7, have been demonstrated to be markers for HPV-driven SCC of the cervix, 50 penis 51 and oropharynx.…”
Section: And References Therein)mentioning
confidence: 99%
“…Fourteen previous studies which reported data on both HPV DNA testing and expression of p16 INK4a as an HPV functional marker were identified for possible inclusion in the meta-analysis. 15,34,[38][39][40][41][42][43][44][45][46][47][48][49] Of these 14 studies, 5 were excluded for the following reasons: Antonsson et al 38 and Koshiol et al 15 HPV DNA1 cases in their ESCC series and hence the study provides no information about relative probabilities of HPV DNA1 and p16 INK4a 1 39 ; and Vaiphei et al 49 did not report specific frequencies of p16 INK4a 1 tumors. The remaining 9 studies, and our own findings (i.e., 10 studies in total), were included in the meta-analysis.…”
Section: Meta-analysis Of Studies With Hpv Dna and P16 Ink4a Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was considered that the expression levels of p53 (1–3), p21 waf1 (4), molecular immunology borstel-1 (MIB-1) (2,5), p16 INK4A (6), cyclin D1 (2,7,8), E-cadherin (8), Bcl-2 (1), tumor necrosis factor (TNF)-α (9), nuclear factor (NF)-κB (10), transforming growth factor (TGF)-β (11), matrix metalloproteinase (MMP)-7 (12), cyclooxygenase (COX)-2 (13,14), epidermal growth factor receptor (EGFR) (15) and hypoxia-inducible factor (HIF)-1α (16) may be used as prognostic factors for ESCC. However, these studies included patients treated with surgery or neoadjuvant chemoradiation therapy (CRT).…”
Section: Introductionmentioning
confidence: 99%